The impact of ownership concentration, bank characteristics, industry specific and countrywide variables, on the performance of the banking sector in Tanzania: A pre-post treasury single account analysis - Goodhope, Hance Mkaro (2024)
In the course of implementing the fiscal policy, the government of Tanzania adopted the Treasury Single Account (TSA) system in early 2016. All government ministries and agents were directed to withdraw and transfer government deposits from commercial banks to the Central Bank of Tanzania through the Treasury Single Account. Notably, since the policy's inception, it has been anticipated that commercial banks' profitability, lending activity, and deposits would decline (World Bank, 2017). Therefore, the present study found it sensible to analyze the TSA’s impact on Tanzania’s bank performance across various bank classifications, bank characteristics, and industry and country-wide variables. The analysis used balanced panel data regression analysis covering 30 banks that were in existence from 2010Q1 to 2020Q4. The 2010 to 2015 phase represented a pre-TSA period, whereas 2016 to 2020 covered the post-TSA phase. Domestic and foreign banks, private and state-owned banks, and large and small banks' performances were paired and revealed mixed results before and after TSA. However, small banks outperformed larger ones in both periods using Return on Asset (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) as financial performance indicators. CAMELS ratings and cost-to-income ratios for all bank classifications recorded mixed results in both periods. Generally, financial statements analysis confirmed that TSA negatively impacted the banking sector’s performance. In light of the above, the study recommends that, among other things, commercial banks' management should invest in searching for proper ways to encourage the public to deposit with commercial banks. Moreover, banks should consider penetrating the rural areas, especially those excluded from accessing formal financial services. Stateowned banks, in particular, are encouraged to divorce from issuing loans to political leaders or government officials without a proper loan recovery mechanism. Employment of advanced technologies and promotion of financial literacy are among other measures to be taken by commercial banks to address the current problem. Keywords: Ownership, Bank Size, Bank Risks, Treasury Single Account (TSA), Tanzania, Performance, ROA, ROE. NIM, CAMELS, Cost-to Income.